Ultrasound bladder wall thickness and detrusor overactivity: a multicentre test accuracy study. (7th February 2017) - Latthe, P; Middleton, L; Rachaneni, S; McCooty, S; Daniels, J; Coomarasamy, A; Balogun, M; Duckett, J; Thakar, R; Goranitis, I; Roberts, T; Deeks, J; et al.
Abstract : Objective: Women with overactive bladder (OAB) often undergo urodynamics before invasive treatments are considered. Ultrasound measurement of bladder wall thickness (BWT) is a less invasive, less expensive and widely available test. It has the potential to diagnose the presence of detrusor overactivity (DO). We aimed to evaluate the accuracy of BWT in the diagnosis of DO. Design: Prospective cohort study. Setting: Twenty‐two UK clinics (university and district general hospitals). Methods: Consecutive eligible women with OAB symptoms had transvaginal ultrasound to estimate BWT (index test). The reference standard for the diagnosis of DO was urodynamic testing with multichannel subtracted cystometry. Main outcome measures: The sensitivity, specificity and likelihood ratios using a BWT threshold of ≥5 mm were used to indicate the presence of DO, and the area under the receiver operating characteristics (ROC) curve to give an overall estimate of BWT accuracy. Results: Between March 2011 and 2013, 644/687 (94%) women recruited had both tests. The mean age was 52.7 years (standard deviation 13.9) and DO was diagnosed in 399/666 (60%) women. BWT had a sensitivity of 43% [95% confidence interval (CI) 38–48%], specificity of 62% (95% CI 55–68%), and likelihood ratios of 1.11 (95% CI 0.92–1.35) and 0.93 (95% CI 0.82–1.06) for positive and negative tests, respectively. The area under the ROC curve was 0.53 (95% CI 0.48–0.57). Extensive sensitivity analyses and subgroup analyses were carried out, but did not alter the interpretation. Conclusions: BWT is not a good replacement test for urodynamics in women with overactive bladder. Tweetable abstract: Bladder wall thickness is not a good replacement test for urodynamics in women with overactive bladder. Tweetable abstract: Bladder wall thickness is not a good replacement test for urodynamics in women with overactive bladder.